Bioconversion of seaweed with white rot fungi for production of protein enriched fish feedstock - Jamal, Parveen; Saheed, Olorunnisola Kola; Jaswir, Irwandi; Ruqayyah, Tijani I.D. (2015)
Viable and economical source of fish feed ingredients remained one of most important factors for a successful and profitable fish production for peasant farmers and industries. Solid state bioconversion (SSB) involving Phanerochaete chrysosporium (P. chrysosporium) was conducted to enrich seaweed with protein. Optimization of processing parameters (moisture content, inoculum size and minerals) with response surface methodology (RSM) showed crude protein increased to 120.29 mg/g. Positive interaction existed among all investigated process parameters and the quadratic model describing the process was significant at p < 0.05. The coefficient of determination –R-squared, of the model was close to unity. The optimum value of moisture content was 73.5% (v/w), 8.5% (v/w) for inoculum size and 7% (v/w) of mineral supplement. Validation of the model showed protein production falling within 10% tolerable point.